These Oppressions Won't Cease An anthology of the political thought of the Cape Khoesan, 1777-1879 : A selection of source documentation in Dutch - Ross, Robert (Wits University Press, 2016)
In the early nineteenth century, the linguistic situation of the Eastern Cape was changing among the Cape Khoesan. Their indigenous language, Cape Khoekhoe, was swiftly being replaced by Dutch or Proto-Afrikaans. The Cape Khoesan articulated their continuous critique of the oppressions of European colonialism through petitions, speeches at meetings and letters to the newspapers. Communication with British officialdom, and in general, was mostly in English or translated into English by the administration.These translations are published in the anthology selected and compiled by Robert Ross, These Oppressions Wonâ t Cease (Wits University Press, 2017). In this supplementary edition, the author has made a compilation of the Dutch texts on which those documents are based. It is a supplement that presents the few original Dutch speeches and letters that survived, thereby giving readers and scholars access to the â raw dataâ . Most importantly, the supplement provides a unique record of the Khoesanâ s resistance, in their own voices, to European settler colonialism.